Acute cardiac injury (ACI) in COVID-19 pneumonia. (2nd May 2022) - Erba, M; Ciarrocchi, F; Dammassa, V; Colombo, C; Mojoli, F; Tavazzi, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Since the SARS-CoV2 break-out many reports focused on the role of cardiovascular system involvement in the patient's outcome(1). However, few descriptions exist including only patients with severe ARDS admitted to general ICU. Methods: We enrolled adult patients with severe ARDS related to COVID-19 infection consecutively admitted to ICU between February 2020 and March 2021. Acute cardiac injury was defined as a rise and fall of cTnI above the 99th percentile (i.e., ≥ 47 ng/L)(2). Hs-TnI was measured at admission and during ICU stay. Echocardiographic examinations were performed at ICU admission and at the time of worst cTnI. Left ventricular (LV) and right ventricular (RV) systolic dysfunction were defined respectively as LV ejection fraction (LVEF) < 50% and as tricuspid annular plane systolic excursion (TAPSE) < 16 mm. Results: A total of 148 patients were included in the analysis. Acute cardiac injury was present in 65 (44.9%) cases at admission. Forty-seven (21.8%) patients had isolated depressed LVEF, 13 (9.0%) had isolated RV systolic dysfunction and 24 (16, 4%) presented with biventricular systolic dysfunction. Eithy-two (56.1%) had a worsening of hs-TNI values during the admission of whom a consensual worsening of LVEF and TAPSE was observed in respectively 32 (21.8%) and 28 (19.2%) patients. Cardiac injury at ICU admission yielded an increased risk of in-hospital mortality (OR 1.30 [95% CI 0.71 – 2.38]) (Figure 1 – left panel) as well as the presence of impaired echocardiography (OR 1.85 [95% CI 1.01 – 3.40]) (Figure 1 – right panel). Worst hs-TNI correlated with worst procalcitonin (PCT) values (p <0.001 r20.81) in case of on-going septic shock and 85 % of patients with RV dysfunction had either evidence of pulmonary thrombus at CT scan or high inspiratory peak pressure (> 30 cmH2O) at mechanical ventilation (respectively, p < 0.001 and p <0.01). Bivariable analysis adjusted for the inverse probability of having an impaired echocardiographic exam confirmed the increased risk of in-hospital mortality in patients with cardiac injury (OR 2.01 [95% CI 1.28 – 3.15]) and in presence of altered echocardiography with RV dysfunction yielding a higher risk (OR 2.42 [95% CI 1.29 – 4.55]) compared with biventricular impairment (OR 1.86 [95% CI 0.87 – 4.00]) and isolated LV dysfunction (OR 1.30 [95% CI 0.77 – 2.19]) (Figure 2). Conclusion: The use of echocardiography for the detection of cardiac dysfunction, has shown a greater correlation with mortality than the identification of acute cardiac damage using laboratory parameters. Of all the parameters obtained with the echocardiography, right ventricular dysfunction demonstrates the greatest correlation with mortality compared to left or biventricular dysfunction. However, the major cause of LV dysfunction in our population occurred during septic shock while RV dysfunction seemed to be due to pulmonary embolism and/or acute cor pulmonale ARDS-related.